1989
DOI: 10.2307/2061257
|View full text |Cite
|
Sign up to set email alerts
|

Mother or Market? Effects of Maternal Employment on the Intellectual Ability of 4-Year-Old Children

Abstract: This article uses the 1986 Children of the National Longitudinal Survey of Youth data set to investigate the impact of maternal employment on children's intellectual ability, as measured at the age of 4 by using the Peabody Picture Vocabulary Test (PPVT). Results from multivariate regression analysis show a statistically significant adverse effect of mother's employment on children's intellectual ability, but only for boys in higher income families. Furthermore, the negative impact was related to the timing of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
220
5
3

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 264 publications
(240 citation statements)
references
References 48 publications
(39 reference statements)
12
220
5
3
Order By: Relevance
“…Although Belsky and Eggebeen (1991) and Baydar and BrooksGunn (1991) found negative effects of early employment, Vandell and Ramanan (1992) found positive effects of early maternal employment for children in low-income families. In a sample of mixed-income families, Desai et al (1989) found that outcomes for children in low-income families were not related to either the child's age when the mother began employment or the mother's pattern of employment.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Although Belsky and Eggebeen (1991) and Baydar and BrooksGunn (1991) found negative effects of early employment, Vandell and Ramanan (1992) found positive effects of early maternal employment for children in low-income families. In a sample of mixed-income families, Desai et al (1989) found that outcomes for children in low-income families were not related to either the child's age when the mother began employment or the mother's pattern of employment.…”
Section: Discussionmentioning
confidence: 95%
“…In that study, 6-year-old children whose mothers changed their employment during the previous 3 years scored significantly lower on teachers' ratings of their cognitive and social competence than children whose mothers were continuously employed. In another study, Desai et al (1989) found no effect of continuous or intermittent maternal employment on 4-year-old children's receptive vocabulary.…”
mentioning
confidence: 88%
See 3 more Smart Citations